Impact of mulch and fertilizer application on yield components, tuber quality and the nutrient uptake of selected potato cultivars under irrigated conditions - Ntuli, Jabulani (My University, 2024)
Integrated nutrient management (INM) in potato production is a promising mitigation strategy to reduce the nutrient-related yield gap. Potato yield and quality are limited in Limpopo by poor soil fertility. This problem is caused by a combination of poor fertilizer application and management, high temperatures and soil degradation. Reductions in potato yields in this region are leading to nationwide potato shortages and price increases. Previous research has shown that INM can maximize potato yield, tuber quality, and limit nutrient losses without degrading the quality of the soil. Therefore, in the present study, INM was centered on fertilizer and mulch application to evaluate growth, yield and nitrogen use efficiency (NUE) responses of various potato cultivars. A field trial was conducted in spring season from September 2022 to February 2023. Four potato cultivars (Mondial, Sababa, Panamera, and Tyson) were evaluated at three fertilizer application rates (0%, 50%, and 100% of the recommended fertilizer application rates from soil test) and two soil cover levels (lucerne grass mulch and no mulch). The selected potato cultivars differed in the potential yield, crop canopy, and time to maturity. These treatments were laid-out as split-split plot in a randomized complete block design replicated three times. For tuber quality and NUE, the experiment was carried out as 3 x 2 x 4 factorial layout, arranged in a completely randomized design (CRD). During the growing season, phenological development and canopy cover were recorded. At and post-harvest, shoots and root biomass, tuber number, fresh mass, dry matter, size grading, and NUE were recorded. Significantly higher tuber yields (41.29 t/ha) were obtained from Panamera cultivar when mulch was applied with the combination of 50% recommended fertilizer application rates. This treatment combination yielded comparable tuber yields as that of 100% recommended fertilizer application rates, mulching and the Panamera cultivar. This suggests that it is possible for farmers to reduce fertilizer application from the recommended rates without compromising their potato yields. Significantly higher NUE (72%) was obtained from Panamera cultivar when mulched without the application of fertilizer. The findings of the study indicated that NUE decreases linearly with increasing N application. The application of 50% fertilizer recommended rate had a significantly higher NUE (31.28%) than 100% recommended fertilizer application rate (19.78%). Very low NUE under 100% recommended N rates indicated that fertilizer saturated states tend to lose more nutrients than unsaturated states. The lowest potato yields (approx. 27 t/ha) were produced by Tyson across all fertilizer levels and Mondial at 50% fertilizer application rate. Mulching increased potato yield by approximately 8 and 16 t/ha under 0 and 50% fertilizer application rates respectively. Generally, mulching induced a significant increasing on time taken to reach physiological maturity, biomass accumulation, tuber fresh mass, number of tubers, and large sized tubers. Across fertilizer treatments, 100% fertilizer application rate significantly increased the shoot dry biomass by 1.39 t/ha relative to 0% fertilizer application rate. Generally, application of 100% fertilizer recommended rate on potato fields resulted in significantly high canopy cover, shoot dry biomass and tuber fresh mass. Potato fields where fertilizers and mulch were not applied, produced significantly lower canopy cover (60.42%) and number of tubers (5.83/ plant). Additionally, secondary interaction of Panamera and Mondial with mulch application showed significantly higher shoot dry biomass (5 t/ha). Growth, quality and yield components of the selected cultivars varied significantly, with Panamera being found to outperform other cultivars. These results suggest that almost the same economic yields can be achieved by applying half the recommended fertilizer rates and using mulch to prevent soil water and nutrient losses. Panamera integrated with 50% fertilizer application rate and mulch application is suitable for sustainably optimizing tuber growth and yield in potato farming. However, the study's findings were limited to environmental conditions prevailing in the study area, single planting season, and hail crop damage. Future research must therefore look at the studied INM in different hail-free seasons and locations.
Thesis (M.Sc. Agriculture (Agronomy)) -- University of Limpopo, 2024
Keywords: Fertilizer rates; Growth; Mulching; Nitrogen use efficiency; Poor soil fertility; Potato cultivar; Tuber quality; Yield; Mulching; Soil fertility; Soils -- Fertilizer movement; Fertilizers; Potatoes -- Varieties; Potato growers